NGHIÊN CỨU CHUYỂN PHA VÀ CÁC TÍNH CHẤT ĐIỆN, TỪ TRONG CÁC HỢP CHẤT La2/3Ca1/3Mn1-xTMxO3- (TM = Cu VÀ Zn) - Khải, Vũ Văn; Sinh, Nguyễn Huy; Tuấn, Nguyễn Anh; Thương, Nguyễn Thị (Vietnam Journal of Science and Technology, 2012)
STUDY ON PHASE TRANSITION, ELECTIC AND MAGNETIC PROPERTIES OF  La2/3Ca1/3Mn1-xTMxO3-d (TM = Cu and Zn) COMPOUNDS The perovskite La1-xCaxMnO3 system has many particular properties with x = 1/3. At this doping concentration, the ferromagnetic-paramagnetic (FM-PM) phase transition temperature (TC) and the metallic-insulator (M-I) phase transtion temperature (Tp) of the compound reach to maximum values. Besides, magnetoresistance effect of the compound is large at low magnetic field. To develop Mn-based perovskite compounds, direct substitutions of Mn by other 3d transition metals (TM) in the La2/3Ca1/3MnO3 compound have been made. The previous studies show that the electronic and magnetic properties of La2/3Ca1/3Mn1-xTMxO3 compounds are variously changed in comparison to these of the La2/3Ca1/3MnO3 compound, but explanation in literature are not enough to shed light on physical mechanisms of these changes. This paper showed new results of the electronic and magnetic properties of La2/3Ca1/3Mn1-xTMxO3 (with TM = Cu and Zn) compounds, in order to clarify more about physical mechanisms underlying the various changes in properties of the compounds by substituting other TM for Mn. It is found that there are three important reasons to explain the changes in the electronic and magnetic properties of La2/3Ca1/3Mn1-xTMxO3 compounds: (i) imperfect ferromagnetic ordering, (ii) decreasing mobility of eg electrons, and (iii) increasing strength of Jahn-Teller distortion by substituting Cu or Zn for Mn.